Kuntaeläkkeiden rahoitus ja kunnalliset palvelut; Financing of Municipal Pensions and Employment in Municipal Services - Jukka Lassila; Niku Määttänen; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2013)
– Municipal employees and private-sector employees in Finland belong to separate earnings-related pension systems. Both systems are financed by contributions from the payroll, and are mostly pay-as-you-go. Thus if a municipality decides to buy services from the private sector, instead of producing them by own employees, the pension contributions will go to the private-sector pension system rather than the municipal pension system. This weakens the financial base of the municipal system and strengthens that of the private-sector system. Outsourcing, however, is not the only factor affecting the relative size of the two systems. Increasing demand for health and long-term care services, caused by population ageing and mostly financed by municipalities, may increase the number of municipal employees substantially during the next 20 years even if outsourcing becomes more widespread. We don't foresee any pension financing problems caused by shifts between municipal and private-sector pension systems in the future. Still the systems should jointly decide how the risk related to future contribution bases is best divided. We also conclude that the current financing rules of the municipal pension system do not significantly affect outsourcing decisions.
Keywords: H55; H22; H75; 330; Municipal pension system; Private-sector pension system; Outsourcing; Pension financing; Altersversorgung im öffentlichen Dienst; Rentenfinanzierung; Privatwirtschaft; Outsourcing; Finnland